2021
DOI: 10.1080/14760584.2021.1951247
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus vaccines performance: dynamic interdependence of host, pathogen and environment

Abstract: Introduction: As of January 2021, rotavirus vaccination programs have been implemented in 109 countries and their use has resulted in a positive impact on rotavirus-related diarrheal hospitalizations and mortality in children below five years of age. Despite these successes, several countries in Africa and Asia where disease burden is high have not yet implemented rotavirus vaccination at all or at a scale sufficient enough to demonstrate impact. This could be, among other reasons, due to poor vaccine coverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 135 publications
1
17
0
Order By: Relevance
“…The differences in vaccine effectiveness have also been observed in connection with oral polio and typhoid vaccines [ 191 ]. Several hosts, pathogen, and environmental factors have been suggested as the driving force for the discrepancies in vaccine performance between the two socioeconomic settings [ 7 , 192 ]. Other barriers to achieving the full potential of the vaccine for global rotavirus disease prevention include age restrictions on vaccine use, concern for safety attributed to intussusception and reversion to virulence in malnourished or immunosuppressed individuals due to the live attenuated nature of the vaccine virus, inhibitory effect of the maternally acquired antibodies against RV, and the cold chain storage requirement, which is difficult to maintain in low resource settings [ 67 ] ( Figure 3 ).…”
Section: Prevention and Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…The differences in vaccine effectiveness have also been observed in connection with oral polio and typhoid vaccines [ 191 ]. Several hosts, pathogen, and environmental factors have been suggested as the driving force for the discrepancies in vaccine performance between the two socioeconomic settings [ 7 , 192 ]. Other barriers to achieving the full potential of the vaccine for global rotavirus disease prevention include age restrictions on vaccine use, concern for safety attributed to intussusception and reversion to virulence in malnourished or immunosuppressed individuals due to the live attenuated nature of the vaccine virus, inhibitory effect of the maternally acquired antibodies against RV, and the cold chain storage requirement, which is difficult to maintain in low resource settings [ 67 ] ( Figure 3 ).…”
Section: Prevention and Controlmentioning
confidence: 99%
“…For instance, a mixed model study of the incidence of rotavirus infection in children from two low-resource settings in India and Malawi showed that children in the former were exposed to rotavirus at a much younger age than those in the latter [ 211 ]. In low resource settings, prevalent factors such as poor sanitation and hygiene, inadequate water supply, and low vaccine coverage have been shown to significantly contribute to higher RV transmission intensity and the early peak of RV incidence compared to their counterparts in high resource settings [ 7 ]. The early and multiple exposures to rotavirus orchestrated by the greater FOI can cause the production of an active immune response similar to maternal antibodies, which may impact vaccine response in infants [ 7 , 202 ].…”
Section: Prevention and Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Host organisms need to evolve sophisticated defense mechanisms against parasites that constantly invent new ways to infect. Host-pathogen interactions are often dynamic, and the disease outcome is commonly dependent on multiple factors including the state of the host, the pathogenic potential of the pathogen and environmental conditions or stressors ( Allam et al, 2013 ; Debasish et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%